2020
DOI: 10.21037/atm.2019.11.115
|View full text |Cite
|
Sign up to set email alerts
|

Logistic regression analyses of factors affecting fertility of intrauterine adhesions patients

Abstract: Background: Intrauterine adhesion (IUA) prevalence is difficult to measure, but appears to have increased over the last few decades. The reproductive outcomes following hysteroscopic adhesiolysis (HA) for moderate-severe IUAs were unsatisfactory, and few studies have analyzed the clinical characteristics pre-, intra-and post-HA to determine the main risk factors for infertility in patients with IUAs. Methods: This retrospective observational study included 406 patients, desiring fertility, who had undergone HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…The hysteroscope went through the cervical canal to the intrauterine cavity, and the adhesions were separated gradually from the central part to the lateral wall. As locating the bilateral fallopian tube ostia is crucial to clarifying the anatomy of the uterine cavity ( Zhao et al, 2020a ), a blunt spreading dissection technique ( Zhang et al, 2015 ) combined with transabdominal ultrasound monitoring was used to increase the visibility of the surgical site. When the intrauterine anatomy was clarified, the IUAs were treated with the cold scissors plowing technique ( Zhao et al, 2020b ) to reconstruct the normal uterine cavity with clearly visible bilateral fallopian tube ostia.…”
Section: Methodsmentioning
confidence: 99%
“…The hysteroscope went through the cervical canal to the intrauterine cavity, and the adhesions were separated gradually from the central part to the lateral wall. As locating the bilateral fallopian tube ostia is crucial to clarifying the anatomy of the uterine cavity ( Zhao et al, 2020a ), a blunt spreading dissection technique ( Zhang et al, 2015 ) combined with transabdominal ultrasound monitoring was used to increase the visibility of the surgical site. When the intrauterine anatomy was clarified, the IUAs were treated with the cold scissors plowing technique ( Zhao et al, 2020b ) to reconstruct the normal uterine cavity with clearly visible bilateral fallopian tube ostia.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that AFS score is closely related to treatment outcome [30][31][32]. In the decision tree, the AFS score before the operation and in the second look is not the main factor to affect live birth.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of IUA has been considered as an important factor relating to the reproductive outcome, and it has already been included in most classification systems. HA appears to be indicated when the extent of the adhesion is moderate to severe or when access to tubal ostia is blocked (5). The smaller proportion of the affected area was associated with the better the prognosis of HA.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread use of hysteroscopy in IUA patients, the reported incidence and diagnosis of IUA have increased significantly, with an average of 2.2 and 36.8%, respectively (1,2), among women of childbearing age. The main risk factors related to IUA are pregnancyrelated, and more than 90% of IUA are closely associated with curettage (3)(4)(5). The main clinical symptoms of IUA include menstrual abnormalities, recurrent miscarriages, and secondary infertility/subfertility.…”
Section: Introductionmentioning
confidence: 99%